Hubungan Pengetahuan Remaja Putri Tentang SADARI dengan Perilaku SADARI Siswi Kelas XII SMKN 1 Cikulur - Indah Nurfazriah; Diah Yuli Anggraeni; Susi Irianti (Lembaga Pengembangan Kinerja Dosen, 2024)
The incidence of breast cancer currently occurs mostly in young women aged 13-25 years, namely 13 cases (4.2%), this is due to a lack of awareness of early detection of breast cancer among teenagers (Sinaga 2016). BSE is an effective way to detect breast cancer early. This research aims to determine the relationship between knowledge of young women about BSE and BSE behavior of Class XII female students at SMKN 1 Cikulur in 2023. The design of this research is descriptive correlation using a cross-sectional approach. The population in this study consisted of 50 respondents. The sampling method used a total sampling of 50 respondents. The data collection method in this research uses a questionnaire. Data analysis used univariate and bivariate analysis with the chis square test. The research results show that there is a relationship between knowledge and BSE behavior of 0.000 (<0.05). The conclusion in this study is that there is a significant relationship between young women's knowledge about BSE and the behavior of breast self-examination (BSE) of class XII female students at SMKN 1 Cikulur in 2023